EXPLORING COFFEE SHOP AND SHARING GENERATION Z COMMUNICATION EXPERIENCES IN SOUTH JAKARTA ON TIKTOK - Rizky Pambudi, Muhammad; Imaddudin (UNIVERSITAS SERAMBI MEKKAH, 2024)
The existence of coffee shops and cafes has become a symbol that represents the lifestyle of young people. The younger generation uses coffee shops for various purposes, including studying with friends, hanging out, and doing works. The experience of visiting a coffee shop has now become an interesting topic to share on social media. This research aims to determine the because of motive and the in order to motive in exploring coffee shops and sharing communication experiences in the style of generation Z in South Jakarta on TikTok social media. The type of research used is qualitative with phenomenological methods to explore phenomena experienced by individuals holistically. Data collection was carried out through observation, semi-structured interviews, and documentation. The research results found that because of motive, Generation Z enjoys visiting coffee shops not only because of their love of coffee, but also because of various other factors that make coffee shops a multifunctional place in their daily lives. In order to motive for sharing experiences at coffee shops via social media TikTok could be because individuals want to express their love for coffee, or share experiences, and provide recommendations to their followers. Further research can be carried out using quantitative methods to complement existing research.